Mechanism, Structure, and Inhibition of O-GlcNAc Processing Enzymes - Gloster, Tracey M. (2010)
The post-translational modification of nucleocytoplasmic proteins with O-linked 2-acetamido-2-deoxy-d-glucopyranose (O-GlcNAc) is a topic of considerable interest and attracts a great deal of research effort. O-GlcNAcylation is a dynamic process which can occur multiple times over the lifetime of a protein, sometimes in a reciprocal relationship with phosphorylation. Several hundred proteins, which are involved in a diverse range of cellular processes, have been identified as being modified with the monosaccharide. The control of the O-GlcNAc modification state on different protein targets appears to be important in the aetiology of a number of diseases, including type II diabetes, neurodegenerative diseases and cancer. Two enzymes are responsible for the addition and removal of the O-GlcNAc modification: uridine diphospho-N-acetylglucosamine:polypeptide β-N-acetylglucosaminyltransferase (OGT) and O-GlcNAcase (OGA), respectively. Over the past decade the volume of information known about these two enzymes has increased significantly. In particular, mechanistic studies of OGA, in conjunction with structural studies of bacterial homologues of OGA have stimulated the design of inhibitors and offered a rationale for the binding of certain potent and selective inhibitors. Mechanistic information about OGT lags a little way behind OGA, but the recent deduction of the structure of an OGT bacterial homologue should now drive these studies forward.